Virtual Prospection of Marine Cyclopeptides as Therapeutics by Means of Conceptual DFT and Computational ADMET - Norma Flores-Holguín; Juan Frau; Daniel Glossman-Mitnik (MDPI AG, 2022)
Bioactive peptides are chemical compounds created through the covalent bonding of amino acids, known as amide or peptide bonds. Due to their unusual chemistry and various biological effects, marine bioactive peptides have garnered considerable research. The effectiveness of a bioactive marine peptide is attributed to its structural features, such as amino acid content and sequence, which vary depending on the degree of action. Cyclic peptides combine several favorable properties such as good binding affinity, target selectivity and low toxicity that render them an attractive modality for the development of therapeutics. The apratoxins are a class of molecules formed by a series of cyclic depsipeptides with potent cytotoxic activities. The objective of this research is to pursue a computational prospection of the molecular structures and properties of several cylopeptides of marine origin with potential therapeutic applications. The methodology will be based on the determination of the chemical reactivity descriptors of the studied molecules through the consideration of the Conceptual DFT model and validation of a particular model chemistry, MN12SX/Def2TZVP/H2O. These studies will be complemented by a determination of the pharmacokinetics and ADMET parameters by resorting to certain cheminformatics tools.